Perception of Difficulties Encountered in Eating Process from European Elderlies' Perspective. Issue 4 (12th May 2016) - Laguna, L.; Mingioni, M.; Maitre, I.; Vanwymelbeke, V.; Pirttijärvi, T.; Artigas, M.G.; Kautola, H.; Järvenpää, E.; Mäenpää, T.; Tahvonen, R.; Grabska‐Kobylecka, I.; Nowak, D.; et al.
Abstract: To maintain wellbeing, independence and nourishment of elderly population, one promising strategy is to provide home care by delivering food using "meals on wheels" (MoW) system. Even when the food is home‐delivered, the difficulties encountered by elderlies during the overall eating process can be a limiting factor. Hence, the objective of this self‐reported study was to explore the difficulty perception in the entire eating process from opening up the package, reheating, hand manipulation and oral processing of the food to bolus swallowing in 405 elderly consumers from five European countries (Finland, France, Poland, Spain and United Kingdom) with three different levels of dependency (category 1: participants living at home with help needed for food purchasing; category 2: participants living at home who need help for meal preparation or meal delivery; category 3: participants living in nursing homes/sheltered accommodation). Frequencies of responses and cross tabulation test were calculated for the difficulties perceived. Results show that the most difficult package to open was the cap irrespective of country or dependency levels (at P < 0.05). Although, glass was the most preferred packaging material, category ( P = 0.034) and country ( P = 0.001) had significant influence. Self‐feeding dependency was correlated with the eating difficulties perceived, category 1 participants did not perceive difficulties in the meal preparation and reported minimal difficulties in the hand manipulation and oral processing (<30%), whilst the difficulties perceived by categories 2 and 3 were significantly higher (∼60% of participants). The insights generated might be helpful for designing efficient MoW systems with appropriate user‐friendly features. Practical Applications: Ageing population is in significant increment in Europe. For elderlies, who are unable to cook due to a various forms of functional incapability, "meals on wheels" (MoW) is a promising approach to extend their independence. In this work, difficulties in the eating process (opening of packaging, meal preparation and self‐feeding) of European elderly population with different levels of self‐eating independency have been investigated using self‐reporting from 405 participants. The most difficult packaging to open was the screw‐cap. Individuals who needed help for only food purchasing did not perceive difficulties in meal preparation and oral processing. Dental status was driving difficulty perception during biting and chewing. It is expected that with the insights generated in this study, MoW operators will improve the packaging in the meals; provide adaptive cutleries and design food with suitable texture ensuring optimum and easy oral processing.